Administrative Factors Affecting Learning Organization in Schools Under Chachoengsao Secondary Educational Service Area Office - Kaewsansuk, Panuwat; Khongthiang, Somsak; Prasertsin, Ujsara (Journal of Graduate MCU KhonKaen Campus, 2025)
This research aimed to: (1) examine the level of becoming a learning organization in secondary schools, (2) investigate the administrative factors influencing the development of a learning organization, (3) construct predictive equations between the influencing factors and the level of being a learning organization, and (4) explore approaches to promote learning organizations in secondary schools. The study was conducted in two phases. In Phase 1, the sample consisted of 351 school administrators and teachers selected through stratified random sampling. The research instrument was a rating-scale questionnaire, and the data were analyzed using percentage, mean, standard deviation, Pearson’s correlation coefficient, and stepwise multiple regression analysis. In Phase 2, the sample included seven school administrators and teachers, and data were collected through semi-structured interviews and analyzed by content interpretation. The results revealed that: 1) the overall level of schools as learning organizations was high; (2) the administrative factors contributing to learning organizations were also rated at a high level; (3) the significant factors positively affecting schools as learning organizations included organizational culture, organizational climate, leadership, and organizational structure, with statistically significant correlations at the .01 level. These factors were used to construct predictive equations in both raw scores and standardized scores; and (4) guidelines for developing learning organizations comprised four aspects: fostering a culture of knowledge sharing, creating a supportive learning climate, promoting leadership that facilitates effective work, and designing flexible organizational structures with reduced operational steps.